Towards a European contract law - Schulze, Reiner; Stuyck, Julien (Sellier European Law Publishers, 2011)
In the decisive political stage of the preparations for an optional European contract law, this volume voices criticism and makes suggestions for improvements to the "Feasibility Study" that is to be the basis of a legislative initiative of the European C.